2004
DOI: 10.1007/s00339-003-2412-1
|View full text |Cite
|
Sign up to set email alerts
|

Model for the hydrogen adsorption on carbon nanostructures

Abstract: The hydrogen sorption capacity of carbon nanostructures was for several years a very controversial subject. Theoretical models have been published demonstrating a great potential for a large hydrogen sorption capacity of carbon nanostructures. Here we present a simple empirical model where condensation of hydrogen as a monolayer at the surface of nanotubes as well as bulk condensation in the cavity of the tube is assumed. The maximum potential amount of hydrogen absorbed according to the model was calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 22 publications
(29 reference statements)
4
64
2
1
Order By: Relevance
“…84 The maximum expected excess capacity can be estimated by assuming that hydrogen adsorbs as a monolayer on the sorbent with a density equal to that of liquid hydrogen. 85 Thus, under this approximation, excess capacity is proportional to the sorbent surface area where the proportionality constant is: 2.28 Â 10 À3 wt% H 2 m À2 g (often referred to as the 'Chahine Rule'). 86 That is, a sorbent possessing a specific surface area of 500 m 2 /g should store up to approximately 1 wt% hydrogen.…”
Section: Gravimetric Capacitymentioning
confidence: 99%
“…84 The maximum expected excess capacity can be estimated by assuming that hydrogen adsorbs as a monolayer on the sorbent with a density equal to that of liquid hydrogen. 85 Thus, under this approximation, excess capacity is proportional to the sorbent surface area where the proportionality constant is: 2.28 Â 10 À3 wt% H 2 m À2 g (often referred to as the 'Chahine Rule'). 86 That is, a sorbent possessing a specific surface area of 500 m 2 /g should store up to approximately 1 wt% hydrogen.…”
Section: Gravimetric Capacitymentioning
confidence: 99%
“…[9][10][11][12] Figure 7 shows the maximum hydrogen uptake at 77 K versus the BET SSA for different crystalline microporous materials. The saturation values for MOFs of the present work and previous results [14] are compared to zeolites.…”
Section: Full Papermentioning
confidence: 99%
“…In fact, it has been previously demonstrated that for other microporous materials, such as carbon materials and zeolites, the maximum hydrogen uptake is correlated to the SSA of the adsorbent. [9][10][11][12] Compared with hydrogen storage in metal hydrides and complex hydrides, physical adsorption has the great advantage of being completely reversible and of exhibiting very fast kinetics. On the other hand, because of the low adsorption enthalpy involved in physisorption, high storage capacities are reached only at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[18] However, hydrogen condensation may only occur under cryogenic conditions. In addition to the uncertain capacity, H 2 adsorption and desorption kinetics may be a limiting factor as well, due to the H 2 diffusion rate inside the carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%